PGC-1α-Mediated Mitochondrial Quality Control: Molecular Mechanisms and Implications for Heart Failure - Chen, Lei; Qin, Yuan; Liu, Bilin; Gao, Meng; Li, Anqi; Li, Xue; Gong, Guohua (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria with structural and functional integrity are essential for maintaining mitochondrial function and cardiac homeostasis. It is involved in the pathogenesis of many diseases. Peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1α), acted as a transcriptional cofactor, is abundant in the heart, which modulates mitochondrial biogenesis and mitochondrial dynamics and mitophagy to sustain a steady-state of mitochondria. Cumulative evidence suggests that dysregulation of PGC-1α is closely related to the onset and progression of heart failure. PGC-1α deficient-mice can lead to worse cardiac function under pressure overload compared to sham. Here, this review mainly focuses on what is known about its regulation in mitochondrial functions, as well as its crucial role in heart failure.